Trinidad. The Country Club - (:unkn) unknown (Bernard Pinnington, 2009)
A giant Samaan tree stands at the driveway and the entrance of the Trinidad Country Club. The postcard is addressed to Mrs. Frank Hammond, Providence, R.I., U.S.A.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Clubs--Trinidad and Tobago; Trees--Trinidad and Tobago; Driveways--Trinidad and Tobago; Trinidad Country Club